Classification and characteristics of atmospheric and climate and environmental conditions that influence the selection of a set of multi-storey buildings - Chernenko, K. (Ways to Improve Construction Efficiency, 2015)
Classification and characteristics atmospheric and climatic , natural conditions (NC), which influences the choice of technology of erection many goidanichgs.